2016
DOI: 10.1007/s00221-016-4749-7
|View full text |Cite
|
Sign up to set email alerts
|

Does state boredom cause failures of attention? Examining the relations between trait boredom, state boredom, and sustained attention

Abstract: Boredom is an important personal and social problem, but the phenomena itself remains poorly understood. Recent work has shown that boredom is highly related to attention, and that this relationship may be instrumental in revealing boredom's causes and consequences. In this paper, experimental findings on trait boredom, state boredom, and sustained attention performance are presented. We demonstrate that trait boredom uniquely predicts sustained attention performance, over and above depression and self-report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 59 publications
10
96
1
1
Order By: Relevance
“…In our study, the No-cues group retrospectively reported a higher level of boredom experienced during the task compared to the Verbal-cues group, but no significant differences in the level of concentration. Whereas empirical work on the association between attention and boredom has largely focused on boredom proneness or trait boredom (e.g., Carriere, Cheyne, & Smilek, 2008;Cheyne, Carriere, & Smilek, 2006;Hunter & Eastwood, 2016;Isacescu, Struk, & Danckert, 2016), the few studies which investigated state boredom reported a positive association with poor sustained attention and mind wandering (Carriere et al, 2008;Hunter & Eastwood, 2016). However, the precise nature of this association has yet to be clarified and specifically the connection between state boredom and mind wandering both assessed "on-line" (during the task) deserves future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the No-cues group retrospectively reported a higher level of boredom experienced during the task compared to the Verbal-cues group, but no significant differences in the level of concentration. Whereas empirical work on the association between attention and boredom has largely focused on boredom proneness or trait boredom (e.g., Carriere, Cheyne, & Smilek, 2008;Cheyne, Carriere, & Smilek, 2006;Hunter & Eastwood, 2016;Isacescu, Struk, & Danckert, 2016), the few studies which investigated state boredom reported a positive association with poor sustained attention and mind wandering (Carriere et al, 2008;Hunter & Eastwood, 2016). However, the precise nature of this association has yet to be clarified and specifically the connection between state boredom and mind wandering both assessed "on-line" (during the task) deserves future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Classic theories of boredom focus on its roots in insufficient external stimulation in the environment. Examples include simple, repetitive tasks that require little to no thought or attention (Cox, 1980;Markey, Chin, Vanepps, & Loewenstein, 2014) and vigilance tasks that require constant attention but little variety (Hunter & Eastwood, 2016;Markey et al, 2014;Thackray et al, 1977). Posner et al (2005) define boredom as low arousal caused by insufficient external stimulation, and van Tilburg and Igou (2016a) argue that low arousal is one of the key components that differentiates boredom from related emotions.…”
Section: Environmental Theories Of Boredommentioning
confidence: 99%
“…People who report high levels of boredom propensity have an avoidant disposition. For example these individuals are more likely to experience depression and anxiety (Chin, Markey, Bhargava, Kassam, & Loewenstein, 2017;Hunter & Eastwood, 2018;Mercer-Lynn, Flora, Fahlman, & Eastwood, 2011;Spaeth, Weichold, & Silbereisen, 2015). Boredom susceptibility reflects aversion to lack of novelty.…”
Section: Introductionmentioning
confidence: 99%